UTILIZATION OF ARTIFICIAL INTELLIGENCE IN MEDICAL EMERGENCY SERVICES: A SYSTEMATIC REVIEW OF OPPORTUNITIES FOR PUBLIC HEALTH ENHANCEMENT - Irma Yudith Ayu Puspita; Noor Lusty Putri Setiawati; Susi Mulyati; Amzal Mortin Andas (STIKes Mandala Waluya Kendari, 2026)
Background: Digital transformation in healthcare, particularly Artificial Intelligence (AI), has created significant opportunities to enhance emergency medical services. However, the clinical effectiveness and public health impact of AI in emergency contexts require comprehensive evidence synthesis. Methods: This systematic review was conducted following PRISMA 2020 guidelines. Literature searches were performed across six databases (PubMed, Scopus, Web of Science, IEEE Xplore, CINAHL, Google Scholar) for publications from 2015 to 2025. Nine empirical studies met the inclusion criteria after rigorous selection. Results: AI demonstrated high diagnostic accuracy (85–96%) for acute conditions such as intracranial hemorrhage and sepsis. AI implementation reduced sepsis mortality by 17% in facilities with high digital maturity. However, medical chatbots showed low accuracy (58%) and potential for harmful recommendations. Ethical issues, algorithmic bias, and infrastructure readiness emerged as major challenges. Conclusion: AI has the potential to improve the accuracy and efficiency of emergency services, but its success depends on infrastructure readiness, ethical governance, and targeted implementation strategies.